Tinnitus: Prospects for Pharmacological Interventions With a Seesaw Model. (August 2018) - Tetteh, Hannah; Lee, Minseok; Lau, C. Geoffrey; Yang, Sunggu; Yang, Sungchil
Chronic tinnitus, the perception of lifelong constant ringing in ear, is one capital cause of disability in modern society. It is often present with various comorbid factors that severely affect quality of life, including insomnia, deficits in attention, anxiety, and depression. Currently, there are limited therapeutic treatments for alleviation of tinnitus. Tinnitus can involve a shift in neuronal excitation/inhibition (E/I) balance, which is largely modulated by ion channels and receptors. Thus, ongoing research is geared toward pharmaceutical approaches that modulate the function of ion channels and receptors. Here, we propose a seesaw model that delineates how tinnitus-related ion channels and receptors are involved in homeostatic E/I balance of neurons. This review provides a thorough account of our current mechanistic understanding of tinnitus and insight into future direction of drug development.